Chimeric antigen receptor T cell therapy targeting CD19-positive leukemia and lymphoma in the context of stem cell transplantation - Schubert, Maria-Luisa; Hückelhoven-Krauss, Angela; Hoffmann, Jean-Marc; Schmitt, Anita; Wuchter, Patrick; Sellner, Leopold; Hofmann, Susanne; Ho, Anthony Dick; Dreger, Peter; Schmitt, Michael (Human gene therapy, 2016)
Novel therapies with chimeric antigen receptor (CAR)-transduced T cells (TCs) sparked new hope for patients with relapsed or refractory CD19-positive leukemia or lymphoma even after stem cell therapies. This review focuses on CARs recognizing the B cell antigen CD19. Both retroviral and lentiviral vectors are used, encoding various anti-CD19 CAR constructs comprising costimulatory molecules such as CD28, CD137/4-1BB, and OX40 either alone (second-generation CARs) or in combination (third-generation CARs). Current, up-to-date published studies on anti-CD19 CAR therapy for acute lymphoblastic leukemia (ALL), chronic lymphocytic leukemia (CLL), and non-Hodgkin lymphoma (NHL) with observed side effects are discussed and an outlook on 58 ongoing trials is given. Clinical responses were achieved in up to 81% of ALL, 50% of CLL, and 40% of NHL patients. Factors with potential influence on the clinical outcome might be the design of the vector, the preconditioning regimen, and the number and quality of transfused CAR TCs. The applicability of clinical CAR TC therapy might include relapse after allogeneic stem cell transplantation (alloSCT), and ineligibility for or “bridging” until alloSCT. In summary, CAR therapy represents a highly promising treatment option even in heavily pretreated patients.